Comparison of Extraction Methods for Recovery of Antioxidant Compounds from White Radish Root (Raphanus sativus L.) and Application as A Natural Preservative in Bottled Beer - Thi Minh Nguyet Nguyen; Pham T. K. Ngoc (Chemical Engineering Transactions, 2022)
Raphanus sativus L. contains many active ingredients, including phenolic compounds, and has potent antioxidant and radical scavenging activity. This study compared quantity and antioxidant capacity of extracts obtained from 4 methods: Ultrasonic-assisted extraction (UAE), enzyme-assisted extraction (EAE), microwave-assisted extraction (MAE), and Soxhlet. The extract obtained from the best extraction method was then applied to preserve bottled beer. The results showed that the EAE method with Viscozyme L. brought the highest extraction efficiency, so it was conducted to optimize the enzyme extraction parameters. The optimal parameters obtained using EAE consisted of 2 stages: pre-treatment with 0.067 FBG (Fungal Beta - Glucanase Units) / gdb (gram of dry basic) of Viscozyme L at 49.3 (C for 66 min, then extraction with ethanol 70 % at 60 (C for 4 h. White radish root powder at 0.5 gdb / L was used as a natural antioxidant to preserve bottled beer from oxidation.